The flavonol-enriched Cistus albidus chloroform extract possesses in vivo anti-inflammatory and anti-nociceptive activity. (14th September 2017) - Tahiri, Ouahiba; Atmani-Kilani, Dina; Sanchez-Fidalgo, Susana; Aparicio-Soto, Marina; Alarcón-de-la-Lastra, Catalina; Barrajón-Catalán, Enrique; Micol, Vicente; Atmani, Djebbar
Abstract: Ethnopharmacological relevance: Cistus albidus L. (Cistaceae) has been traditionally used to treat various inflammatory diseases, but no systematic studies on the anti-inflammatory and anti-nociceptive actions of C. albidus and its putative mechanism have been reported. We aimed to explore the anti-inflammatory and anti-nociceptive effects of this plant and to characterize its polyphenolic composition by liquid chromatography coupled to mass spectrometry (MS). Materials and methods: A chloroform extract derived from C. albidus leaves was obtained by solid-liquid and liquid-liquid extraction. The tail immersion test and acetic-acid-induced writhing test were used to evaluate the anti-nociceptive action, while the experimental λ-carrageenan-induced paw edema model was used to test the anti-inflammatory action. Changes in cyclooxygenase (COX)-2 and inducible nitric oxide synthase (iNOS) expression, as well as the role of mitogen-activated protein kinases (MAPKs) and the nuclear transcription factor kappa B (NF-kB) signaling pathways on lipopolysaccharide (LPS)-stimulated murine peritoneal macrophages were analyzed by western blotting. HPLC with diode array detection coupled to tandem mass spectrometry detection with electrospray ionization (HPLC-DAD-ESI-MS/MS) was performed to determine the phytochemical profile of the extract. Results: Significant anti-nociceptive activity was observed both in the tail immersion (59.63% reduction at 120 min) and in the acetic acid (65.94% inhibition) tests at 100 mg/kg. The extract (50 mg/kg) exhibited a substantial reduction in paw edema (51.6%) and significantly inhibited nitrite generation (72.62%) without affecting cell viability of LPS-stimulated murine peritoneal macrophages. These results were concomitant with a down-regulation of the pro-inflammatory enzymes COX-2 and iNOS in extract-treated macrophages and a decrease in p38 MAPK phosphorylation. HPLC-DAD-ESI-MS/MS analysis revealed that flavonols such as kaempferol and quercetin derivatives were potentially responsible for such effects. Conclusion: These results support the widespread use of C. albidus in popular medicine and indicate that this plant has therapeutic potential with analgesic and anti-inflammatory properties based on the presence of flavonol derivatives. Graphical abstract: